Analysis of a horse simulator`s locomotion by inertial sensors - Prin-Conti, D.; Simon, A.; Bertucci, W.; Debray, K. (Computer Methods in Biomechanics and Biomedical Engineering, 2017)
To determine the imbalance of each, horse or rider, the balance`s quality of the rider will be expertise and improve by an adjusted simulator, without the unpredictable reactions of a real horse. The use of an equestrian simulator enables the rider to improve his technique without the different risks linked to the practice on a real horse. These simulators are sold without any specification regarding the operation, validity and regularity. Such a device has to be however controlled in terms of movement stability (Mager-Maury et al. 2012). This study aims to verify this aspect on a mechanical horse by using an inertial measurement unit (IMU), in order to improve the rider`s training programs by adapting the different protocols to the inter-individual differences between the riders. This will allow us to be relevant to the session`s repeatability and riders monitoring. The unpredictable reactions of a real horse prevent the accuracy and secure rider`s balance studies. The weight and rider`s experience has an effect on the horse`s behaviour (Clayton 1997; Eckardt et al. 2014).